2021
DOI: 10.1007/s00520-021-06440-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial well-being and supportive care needs of cancer patients and survivors living in rural or regional areas: a systematic review from 2010 to 2021

Abstract: Purpose To summarise what is currently known about the psychosocial morbidity, experiences, and needs of people with cancer and their informal caregivers, who live in rural or regional areas of developed countries. Methods Eligible studies dating from August 2010 until May 2021 were identified through several online databases, including MEDLINE, EMBASE, PsychINFO, and RURAL (Rural and Remote Health Database). Results were reported according to the PRISMA guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 84 publications
3
72
0
Order By: Relevance
“…The results are consistent with many reports of the positive aspects of rurality, such as high levels of community engagement and support [28] and the high self-efficacy found in the surveys conducted in our wider study [35]. The other factors contributing to the survivorship experience, which was previously found to have an effect on cancer survivors, have been mirrored by these results, and these include social support, practical challenges, access issues, and persistent symptoms [9,18,20,33].…”
Section: Findings In Context Of the Academic Literaturesupporting
confidence: 91%
See 4 more Smart Citations
“…The results are consistent with many reports of the positive aspects of rurality, such as high levels of community engagement and support [28] and the high self-efficacy found in the surveys conducted in our wider study [35]. The other factors contributing to the survivorship experience, which was previously found to have an effect on cancer survivors, have been mirrored by these results, and these include social support, practical challenges, access issues, and persistent symptoms [9,18,20,33].…”
Section: Findings In Context Of the Academic Literaturesupporting
confidence: 91%
“…Pre-existing factors, such as gender and SES, have been shown to affect cancer outcomes and experiences [ 15 , 45 ], and our analysis highlights examples of this. Both personal and environmental factors feed into how people cope and into their cancer-related self-efficacy, and it has been found that rural populations experience higher levels of community support and have generally higher self-efficacies [ 18 , 35 ]. This is reflected by the positive experiences of communities in rural areas in this study, finding that most participants relied on community support to support their coping and self-management skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations